Quality of Life Among Older Adults Living with HIV: A Literature Review - Shinta Elrica Saniyya; Nova Ardianto; Maya Trisiswati (Medical and Health Journal, 2026)
Advances in antiretroviral therapy have extended the life expectancy of people living with HIV, leading to a growing population of older adults with this condition who face age-related biological decline alongside persistent psychosocial pressures that may reduce their quality of life. This review was conducted to describe the quality of life of older adults living with HIV and to examine the psychosocial factors influencing it based on research published in the past five years. A literature review approach was employed by searching several online databases and selecting studies published between 2019 and 2025 that focused on quality of life and psychosocial aspects among individuals aged 50 years and older living with HIV. Six studies met the inclusion criteria and show a consistent pattern indicating that the quality of life of older adults with HIV is shaped by psychosocial conditions such as stigma, depression, and limited social support, all of which contribute to diminished well-being. Conversely, protective factors such as resilience and community support play a crucial role in enhancing psychological health and improving overall quality of life. These findings highlight that the well-being of older adults living with HIV is strongly influenced by their psychosocial environment, and emphasize the need for interventions that strengthen social support and foster resilience to promote better quality of life within this population.